The University and the Algorithmic Gaze - Gourlay, Lesley (Bloomsbury Academic, 2025)
This open access book takes an innovative and critical look at the ways in which digital data and algorithms are changing the face of higher education in multiple ways. It examines their impact at both the macro scale of universities and systems worldwide, but also at the more subtle level of effects on academics and students. In doing so, it focuses on the day-to-day life of the university, examining how the digital is changing the way that we communicate, learn, and create new knowledge. As well as exploring the role of ‘big data’ and learning analytics, the book also focuses on areas of academic life not normally considered to be part of datafication, such as the physical structures of surveillance on campus and the ways in which systems of ‘quality’ in research can morph into regimes of surveillance and algorithmic discipline. Taking an interdisciplinary perspective, the volume interweaves insights from Surveillance Studies, Science and Technology Studies and Postphenomenology. . Its wide-ranging analysis generates fresh, critical new insights into the nature of communication, semiosis, textual practices, subjectivities and knowledge practices at this dynamic and fast-moving juncture in the history and development of higher education worldwide. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by University College London, UK.